Large Oblate Hemispheroidal Ruthenium Particles Supported on Calcium Amide as Efficient Catalysts for Ammonia Decomposition. Issue 31 (8th May 2018) - Kishida, Kazuhisa; Kitano, Masaaki; Inoue, Yasunori; Sasase, Masato; Nakao, Takuya; Tada, Tomofumi; Abe, Hitoshi; Niwa, Yasuhiro; Yokoyama, Toshiharu; Hara, Michikazu; Hosono, Hideo
Abstract: Ammonia decomposition is an important technology for extracting hydrogen from ammonia toward the realization of a hydrogen economy. Herein, it is reported that large oblate hemispheroidal Ru particles on Ca(NH2 )2 function as efficient catalysts for ammonia decomposition. The turnover frequency of Ru/Ca(NH2 )2 increased by two orders of magnitude when the Ru particle size was increased from 1.5 to 8.4 nm. More than 90 % ammonia decomposition was achieved over Ru/Ca(NH2 )2 with large oblate hemispheroidal Ru particles at 360 °C, which is comparable to that of alkali‐promoted Ru catalysts with small Ru particle sizes. XAFS analyses revealed that Ru particles are immobilized on Ca(NH2 )2 by Ru−N bonds formed at the metal/support interface, which lead to oblate hemispheroidal Ru particles. Such a strong metal–support interaction in Ru/Ca(NH2 )2 is also substantiated by DFT calculations. The high activity of Ru/Ca(NH2 )2 with large Ru particles primarily originates from the shape and appropriate size of the Ru particles with a high density of active sites rather than the electron‐donating ability of Ca(NH2 )2 . Abstract : Bigger is better : Oblate hemispheroidal Ru particles on Ca(NH2 )2 are efficient catalysts for ammonia decomposition. The turnover frequency of Ru/Ca(NH2 )2 increases by two orders of magnitude on increasing the Ru particle size from 1.5 to 8.4 nm (see figure). Formation of large oblate hemispheroidal Ru particles on Ca(NH2 )2 is due to the strong metal–support interaction between Ru and N atoms of the Ca(NH2 )2 surface, and their high density of active sites accounts for the high catalytic performance of Ru/Ca(NH2 )2 in ammonia decomposition.